Toxoplasma gondii induces prolonged host epidermal growth factor receptor signalling to prevent parasite elimination by autophagy: Perspectives for in vivo control of the parasite. (17th July 2019) - Lopez Corcino, Yalitza; Gonzalez Ferrer, Shekina; Mantilla, Luz Eliana; Trikeriotis, Sophia; Yu, Jin‐Sang; Kim, Steven; Hansen, Samuel; Portillo, Jose‐Andres C.; Subauste, Carlos S.
Abstract: Toxoplasma gondii causes retinitis and encephalitis. Avoiding targeting by autophagosomes is key for its survival because T . gondii cannot withstand lysosomal degradation. During invasion of host cells, T . gondii triggers epidermal growth factor receptor (EGFR) signalling enabling the parasite to avoid initial autophagic targeting. However, autophagy is a constitutive process indicating that the parasite may also use a strategy operative beyond invasion to maintain blockade of autophagic targeting. Finding that such a strategy exists would be important because it could lead to inhibition of host cell signalling as a novel approach to kill the parasite in previously infected cells and treat toxoplasmosis. We report that T . gondii induced prolonged EGFR autophosphorylation. This effect was mediated by PKCα/PKCβ ➔ Src because T . gondii caused prolonged activation of these molecules and their knockdown or incubation with inhibitors of PKCα/PKCβ or Src after host cell invasion impaired sustained EGFR autophosphorylation. Addition of EGFR tyrosine kinase inhibitor (TKI) to previously infected cells led to parasite entrapment by LC3 and LAMP‐1 and pathogen killing dependent on the autophagy proteins ULK1 and Beclin 1 as well as lysosomal enzymes. Administration of gefitinib (EGFR TKI) to mice with ocular and cerebral toxoplasmosis resulted in disease control that was dependent on Beclin 1. Thus, T . gondii promotes its survival through sustained EGFR signalling driven by PKCα/β ➔ Src, and inhibition of EGFR controls pre‐established toxoplasmosis.